Bio-paraffin from Soybean Oil as Eco-friendly Alternative to Mineral Waxes - Romero, Sandra Zulema (2021)
Blends of fully and partial hydrogenated soybean oil, with 50/50 and 80/20 wt %, were chemically interesterified. The composition-texture relationships were investigated and established for the set of investigated materials. The raw materials, the original and interesterified blends, were analyzed in terms of their fatty acid and triacylglycerol compositions by gas chromatography. All materials were characterized by differential scanning calorimetry (DSC), polymorphic forms were characterized by X-ray diffraction (XRD), crystalline structures were characterized by polarized light microscopy (PLM), and textures were characterized by penetration testing. Interesterification caused a rearrangement of triacylglycerol species, reducing the concentration of trisaturated, triunsaturated, and diunsaturated triacylglycerols, increasing the amount of monounsaturated triacylglycerol, and resulting in a lowering of melting points as compared with the original blends. This modification in the chemical composition clearly changed the crystallization behavior, producing reductions in crystal size, alterations in crystalline polymorphism, and increases in plasticity in the blends. Interesterified materials displayed melting and textural characteristics suited for potential mineral wax substitutes.